Courses
Courses for Kids
Free study material
Free LIVE classes
More LIVE
Join Vedantu’s FREE Mastercalss

# If $\sin 3\theta = \cos \left( {\theta - {6^0}} \right)$, where $3\theta$ and $\left( {\theta - {6^0}} \right)$ are acute, find the value of $\theta$. Verified
364.8k+ views
Hint- Here, we will be using the trigonometric function $\sin \phi = \cos \left( {{{90}^0} - \phi } \right)$.

Given, $\sin 3\theta = \cos \left( {\theta - {6^0}} \right){\text{ }} \to {\text{(1)}}$
We know that $\sin \phi = \cos \left( {{{90}^0} - \phi } \right)$ where $\phi$ is an acute angle.
As, $3\theta$ is also acute angle so we can write $\sin 3\theta = \cos \left( {{{90}^0} - 3\theta } \right)$
Therefore, equation (1) becomes
$\Rightarrow \cos \left( {{{90}^0} - 3\theta } \right) = \cos \left( {\theta - {6^0}} \right) \Rightarrow {90^0} - 3\theta = \theta - {6^0} \Rightarrow 4\theta = {96^0} \\ \Rightarrow \theta = {24^0} \\$
Further also we have to check whether the angles $3\theta$ and $\left( {\theta - {6^0}} \right)$ are
coming acute angles or not.
For $\theta = {24^0}$, $3\theta = {72^0}$ and $\left( {\theta - {6^0}} \right) = {18^0}$
That means both the angles are coming acute so $\theta = {24^0}$ which is the required acute angle.

Note- In these types of problems, we convert both the LHS and the RHS of the given equation into one
trigonometric function and then compare the angles to solve for the unknown.
Last updated date: 27th Sep 2023
Total views: 364.8k
Views today: 9.64k